The complete chloroplast genome of Sesbania cannabina - Tan, Wei (Mitochondrial DNA B Resour, 2019)
Sesbania cannabina is an annual plant widely distributed in south China, southeast Asia, and Australia. In the present study, we sequenced the complete chloroplast genome of S. cannabina, which is 153,978 bp in length and it is characterized by a typical quadripartite structure composed of a LSC (85,406 bp) and SSC (19,112 bp) region interspersed by a pair of 23,730 bp IR regions. It encodes 125 genes, comprising 81 protein-coding genes, 8 rRNA genes, and 36 tRNA genes. Phylogenetic analysis confirmed the position of S. cannabina within the subfamily Papilionoideae.